The Effect of Information Technology and Knowledge Sharing on Performance - Praditya, Rayyan (Journal of Industrial Engineering & Management Research, 2019)
This study aims to analyze the effect of information technology and knowledge sharing on employee performance. This research was conducted at the Puskesmas in Pati Regency, where the data was collected using a questionnaire. The sample of this study was the Karaywana Puskesmas in Pati Regency, amounting to 160 people, while for the data analysis technique, this study used path analysis with SPSS 21. The results of this study indicate that information technology has a significant effect on knowledge sharing, but has no significant effect on employee performance, knowledge sharing has a significant effect on employee performance and knowledge sharing acts as a mediator full of the influence of information technology on employee performance.